2021
DOI: 10.1016/j.medcli.2021.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Long-term consequences of SARS-COV2 infection: Long-Covid patterns and possible public health implications

Abstract: Since January 2020 Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre -including this research content -immediately available in PubMed Central and other publicly funded repositories, such as the WHO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…As with previous studies, 15 three patterns of long covid were observed: organ specific symptoms, such as reduced exercise capacity, anosmia and ageusia, chest pain, palpitations, headache, rash, myalgia, and arthralgia; objective findings of impaired mental health and wellbeing, such as anxiety, depression, non-organic pain, and fatigue; and neurocognitive impairment seen more commonly in cohorts admitted to hospital. 9 16 17 In Whittaker and colleagues' study, patients admitted to hospital with covid-19 were older than those not admitted.…”
supporting
confidence: 81%
“…As with previous studies, 15 three patterns of long covid were observed: organ specific symptoms, such as reduced exercise capacity, anosmia and ageusia, chest pain, palpitations, headache, rash, myalgia, and arthralgia; objective findings of impaired mental health and wellbeing, such as anxiety, depression, non-organic pain, and fatigue; and neurocognitive impairment seen more commonly in cohorts admitted to hospital. 9 16 17 In Whittaker and colleagues' study, patients admitted to hospital with covid-19 were older than those not admitted.…”
supporting
confidence: 81%